Behavior intention for athlete post retirement life using Acylic Behavior Change Diagram (ABCD) - Irza Hanie, Abu Samah; Intan Maizura, Abd Rashid; Saraih Ummi, Naiemah; Wan Ahmad Fauzi, Wan Husain; Mohammad Harith, Amlus; Hariri, Hamzah (AIP Publishing, 2023)
Athletes quality of life is very important to be look at. The reason is that the transition they experience is different from other people because most athletes experiencing a drastic change of routine once they retired. And this could lead the psychological problem for example having anxiety, nervousness and worry about their life without sport. With recent challenges due to the recent pandemic of Covid-19, the chances to escalate athlete exit from sport voluntary or involuntary is there. Using JAMOVI, Therefore, this study adopted Acyclic Behaviour Change Diagram (ABCD) to proposing the behaviour intervention and processes of transition in understanding the flows of voluntary and involuntary retirement in sport. The current study contributes toward the literature in understanding the diagram and flow of athlete retirement which, many researches before this were only proposing a theoretical framework and lacking in providing detail workflow processes.